Student Teachers' Motivation toward Participation in the Professional Development Programs - Ali A. Al-Barakat; Bushra A. Alakashee; Samih M. Al Karasneh; Abdalla F. El-Mneizel; Jamal F. Ahmad; Sami S. Al-Qatawneh (Emerging Science Journal, 2023)
The twenty-first century is witnessing an increasing and clear interest in studying the relationship between student teachers' motivation and their participation in professional development programs. This study was designed to find out the student teachers' motivation toward participation in professional development programs and to identify the role of motivation in influencing the ambition, perseverance, and desire of student teachers to be effective and active in carrying out activities and tasks. The descriptive survey design was employed, 75 student teachers were chosen to participate, and data were collected using a developed instrument after ensuring its validity and reliability. The results of the study showed that the level of student teachers' motivation toward participation in professional development programs was very high and that they are aware of the fact that professional development programs are the most effective means for developing their ambition, perseverance, and desire to participate in activities and tasks. Based on these findings, a set of conclusions and recommendations were drawn. Doi: 10.28991/ESJ-2023-SIED2-06 Full Text: PDF